Executive functions in elderly men - Liu, Mu-En (Springer Netherlands, 2011)
The executive function deficit is greater in depressed patients with cardiovascular disease than in depressed patients without cardiovascular disease. Late-life depression is said to have a vascular etiology and would worsen the executive function. A cross-sectional design was used for this study. The study was done in outpatient clinics of Kaohsiung Veterans General Hospital and National Cheng Kung University Hospital, Taiwan. Three hundred thirty-five older elderly men (>75 years old) were chosen as study participants, some military veterans and some not. The mini-mental state examination was used to exclude those suspected of dementia, the Mini-International Neuropsychiatric Interview to screen those undergoing a current major depressive episode, and the revised Geriatric Depression Scale Short Form to measure the severity of depression. Specialist physicians obtained past histories of medical illnesses through chart reviews, history taking, and health examinations. Elderly men with major depression comorbid with cardiovascular disease had worse executive functions. Executive function impairment is greater in elderly men diagnosed with major depression comorbid with cardiovascular disease than in those without cardiovascular disease.